Link adjustment for spatial multi-loop deployable structures considering redundant constraints based on multi-objective discrete optimization. (July 2019) - Zhao, Qiangqiang; Guo, Junkang; Yu, Dewen; Chen, Feifei; Hong, Jun; Liu, Zhigang
Because of the existence of link errors, assembly deviations, and redundant constraints, link adjustments for deployable structures must be implemented during the assembly process to ensure accurate performance and deployable reliability. Thus, this study proposes an optimization method to conduct quantitative link adjustments for spatial multi-loop deployable structures considering redundant constraints. First, the equations of the deformation compatibility are derived based on static analysis. Second, by formulating the objective functions of surface accuracy and strain energy, a multiobjective discrete optimization model of link adjustment, subjected to the equations of the deformation compatibility and adjustable scopes of the support links, is established accordingly. Third, the optimization model is solved using the successive Taguchi approach, which uses the grey relational analysis coupled with principal component analysis as the multicriteria decision-making model, leading to the optimal adjustment for each link. Finally, a numerical example is presented to verify the validity of the proposed method.